Safety and Efficacy of Everolimus Plus Exemestane in Postmenopausal Women with Treatment-refractory Hormone Receptor-positive, Human Epidermal Growth Factor Receptor 2-negative Advanced Breast Cancer: Analysis from EVEREXES Taiwan Subset - Yuan-Ching Chang; Kun-Ming Rau; Dar-Ren Chen; Tsu-Yi Chao; Ming-Feng Hou; Chiun-Sheng Huang* (Journal of Cancer Research and Practice)
Background: This phase IIIb, open-label study enrolled patients from nine Asian and Middle Eastern countries to evaluate the safety and efficacy of the combination therapy in underrepresented patient populations from the Breast Cancer Trials of Oral Everolimus-2 (BOLERO-2). Here, we report the Taiwanese subset data. Materials and Methods: The primary objective was to evaluate the safety and tolerability of everolimus and exemestane (EVE + EXE); the secondary endpoints included progression-free survival (PFS), response rates, and clinical benefit rate. Postmenopausal patients who had metastatic, recurrent, or locally advanced hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2−) advanced breast cancer (ABC) refractory to nonsteroidal aromatase inhibitor (NSAI) and had received EVE + EXE were recruited. Results: From March 2013 to October 2014, 235 postmenopausal women were enrolled in EVEREXES. Taiwanese patients (n = 22) had similar baseline characteristics compared with BOLERO-2 cohort; most (17/22) had discontinued due to disease progression. Only two patients dropped out due to unacceptable adverse events (AEs) despite worse stomatitis (any 77.3%; grade 3/4, 18.2%). Other common AEs included pneumonitis (45.5%), rash (27.3%), and hyperglycemia (9.1%). PFS and safety in EVEREXES compared favorably with BOLERO-2, especially among Taiwanese patients (median: 49 weeks; 95% confidence interval = 19.3–82.0). Conclusion: Although EVEREXES had a small Taiwanese population, the encouraging outcomes compared with BOLERO-2 showed that EVE + EXE is safe for Taiwanese patients with HR+ HER2− ABC who progressed on NSAIs. Large-scale verification is warranted.